2015
DOI: 10.1007/s12043-015-0984-x
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous transport effects and possible environmental symmetry ‘violation’ in heavy-ion collisions

Abstract: Abstract. The heavy ion collision provides a unique many-body environment where local domains of strongly interacting chiral medium may occur and in a sense allow environmental symmetry "violation" phenomena. For example certain anomalous transport processes, forbidden in usual medium, become possible in such domains. We briefly review recent progress in both the theoretical understanding and experimental search of various anomalous transport effects (such as the Chiral Magnetic Effect, Chiral Separation Effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 147 publications
3
89
0
Order By: Relevance
“…What's more, all the hydrodynamical quantities should be both temperature and the axial chemical potential dependent. We can also use the method developed in this work to investigate the newly found anomalous effects [77] (such as the Chiral Magnetic Effect, Chiral Separation Effect and so on) analytically. …”
Section: Discussion and Outlooksmentioning
confidence: 99%
“…What's more, all the hydrodynamical quantities should be both temperature and the axial chemical potential dependent. We can also use the method developed in this work to investigate the newly found anomalous effects [77] (such as the Chiral Magnetic Effect, Chiral Separation Effect and so on) analytically. …”
Section: Discussion and Outlooksmentioning
confidence: 99%
“…The recent reviews of these anomalous transports can be found in Refs. [93,[121][122][123][124][125][126].…”
Section: Magnetic-field Induced Anomalous Transports In Heavy-iomentioning
confidence: 99%
“…Pseudovector field-driven effects have attracted more and more interests recently [1][2][3][4]. As a parityeven and time-reversal-odd field, numbers of novel and non-trivial phenomena would be driven by it,such as chiral magnetic effect [1,2,5,6].…”
Section: Introductionmentioning
confidence: 99%